PRIMERA DESCRIPCIÓN DEL MACHO DE Mastophora extraordinaria HOLMBERG, 1876 (ARANEAE: ARANEIDAE), CON NOTAS SOBRE SU HISTORIA NATURAL Y DISTRIBUCIÓN POTENCIAL DE LA ESPECIE - Costa, María Cecilia; Hagopián, Damián; Simo, Miguel Ramón; Guerrero, José Carlos; Laborda, Alvaro (Boletín de la Sociedad Zoológica del Uruguay, 2021)
The genus Mastophora Holmberg, 1876 is represented by 50 species that are distributed mainly in America and the Antilles. Males are much smaller than females and are not described in more than half of the known species of the genus. The high specificity of their diet (moths) and the technique which females use to capture their prey have been recorded in representatives of the genus. The objectives of this contribution are: to describe for the first time the male of Mastophora extraordinaria Holmberg, 1876, the type species of the genus, to provide images of live specimens and genitalia of both sexes and to give data of natural history, development, feeding and its potential distribution. We performed observations in the field and in the laboratory we maintained females with their egg-sacs until the adulthood of the males occurred. Males of M. extraordinaria are distinguished by having a short and curved embolus and median apophysis with a broad base and hook shaped at the apex. The species was founded in tree foliages in natural forests or in urban gardens. Literature data and new distribution records show that the species has a peripampasic distribution.